Simulation of the ATLAS ITk strip endcap modules for testbeam reconstruction and analysis - Atkin, Ryan Justin (Department of Physics, 2020)
The Large Hadron Collider (LHC) is planned to be upgraded to the High Luminosity LHC (HL-LHC), increasing the rate of collisions and producing more particles passing through the detectors. This increased production rate will require upgrades to the detectors in order to cope with the large increase in data collection and radiation as well as improving the tracking and particle reconstruction in the higher occupancy environment. A major upgrade to ATLAS, one of the LHC detectors, will be replacing the current Inner Detector (ID) with a fully silicon semi-conductor based Inner Tracker (ITk). The research and development phase of the ITk requires a simulation of the sensors for performance simulations and testing the sensors in testbeams. The ITk strip end-cap sensors will use radial geometries, however the current testbeam telescope simulation software (AllPix) and reconstruction software (EUTelescope) are designed with cartesian geometries. Presented is the work behind implementing a radial geometry for one of the ITk strip endcap sensors, the R0 module, in the simulation software of Allpix and the reconstruction software of EUTelescope. Included in this work is the simulation of the propagation of the charge deposited in the sensor by the beam. The simulated data, as well as data from the actual EUDET testbeam telescope at DESY, Hamburg are both reconstructed with the same reconstruction software and analysed using the same post-reconstruction software. A comparison of the simulation to experiment is then performed, in particular to study the residuals, efficiency and charge sharing of the R0 module.